Niosomal Serum Containing an Optimized Blend of Thai Herbal Extracts: Physicochemical Characterization and Clinical Performance on Skin Hydration and Pigmentation - Oraphan Anurukvorakun; Witchuda Sukjoi; Jaroenporn Chokboribal (Cosmetics, 2026)
This study optimized a Thai herbal blend inhibiting tyrosinase and evaluated its delivery in niosomal serum versus a corresponding non-niosomal (free extract) serum. The physicochemical properties, antioxidant and tyrosinase-inhibitory activities, stability, and clinical effects of the two serums were assessed in an 8-week study in healthy volunteers. Herbal combinations were screened using a two-level, five-factor design with tyrosinase inhibition as the response, and the optimized extract ratio (3:2:3:2:2, w/w) was incorporated into conventional, liposomal, and niosomal formulations. Vesicle characterization and in vitro performance supported the niosomal serum for clinical comparison with the corresponding non-niosomal product. The niosomal serum showed appreciable DPPH radical-scavenging activity (IC50 32 mg/mL), whereas the conventional serum exhibited the highest tyrosinase inhibition (IC50 8.3 mg/mL). Clinically, 30 of 50 randomized volunteers completed the 8-week trial and were included in the efficacy analysis. The niosomal serum produced more consistent improvements in skin hydration and transepidermal water loss, with significant benefits over the non-niosomal (free extract) serum at selected mid-to-late time points. Erythema decreased significantly with both formulations, whereas melanin reduction was modest. These findings support the use of niosomal formulations containing combined Thai herbal extracts as a practical strategy to enhance moisturization and barrier support in skincare formulations.